2021
DOI: 10.5194/acp-21-18029-2021
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of Saharan dust to the ice-nucleating particle concentrations at the High Altitude Station Jungfraujoch (3580 m a.s.l.), Switzerland

Abstract: Abstract. The ice phase in mixed-phase clouds has a pivotal role in global precipitation formation as well as for Earth's radiative budget. Above 235 K, sparse particles with the special ability to initiate ice formation, ice-nucleating particles (INPs), are responsible for primary ice formation within these clouds. Mineral dust has been found to be one of the most abundant INPs in the atmosphere at temperatures colder than 258 K. However, the extent of the abundance and distribution of INPs remains largely un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 86 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…Studies have shown that soil wind erodibility is also affected by soil texture and organic matter (Motaghi et al, 2020). Soil organic matter and clay can improve soil aggregation by gathering soil particles together and binding them, leading to larger aggregates, which are more resilient against wind erosion (Charman and Murphy, 2000;Ghaderi and Ghodoosi, 2005;Colazo and Buschiazzo, 2010;Mahmoodabadi and Ahmadbeigi, 2013;Sirjani et al, 2019). The high EF of Sa sheets (Fig.…”
Section: Correlation Between Soil Properties Of Playa Surfaces and Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that soil wind erodibility is also affected by soil texture and organic matter (Motaghi et al, 2020). Soil organic matter and clay can improve soil aggregation by gathering soil particles together and binding them, leading to larger aggregates, which are more resilient against wind erosion (Charman and Murphy, 2000;Ghaderi and Ghodoosi, 2005;Colazo and Buschiazzo, 2010;Mahmoodabadi and Ahmadbeigi, 2013;Sirjani et al, 2019). The high EF of Sa sheets (Fig.…”
Section: Correlation Between Soil Properties Of Playa Surfaces and Th...mentioning
confidence: 99%
“…Mineral dust particles have been found to be the dominant INP type at temperatures below 258 K (Hoose and Möhler, 2012;Murray et al, 2012). Indeed, Brunner et al (2021) estimated that 97 % of all INPs active at 243 K at the high-altitude station at Jungfraujoch, Switzerland, are dust particles. At higher temperatures, biological particles are considered more relevant (Conen et al, 2011;Kanji et al, 2017;Testa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the Jungfraujoch Research Station (approximately 140 km WSW of Weissfluhjoch) released a Saharan dust event warning only at 13:37 UTC. Brunner et al (2021) reported that the determination of a Saharan dust event varies based on the underlying parameter used as proxy. The three samples with higher INP concentrations (orange crosses on 18 and 19 February in Fig.…”
Section: Inp Concentration Comparisonmentioning
confidence: 99%
“…Mineral dust has been found to be the prevailing INP type at temperatures below 258 K (Kanji et al, 2017;O'Sullivan et al, 2018;Brunner et al, 2021), while biological particles such as bacteria, pollen, fungi, and proteins are considered to dominate ice nucleation at higher temperatures (DeMott and Prenni, 2010;Després et al, 2012;Kanji et al, 2017). Feldspar, quartz, and clay minerals have proven to be relevant mineral INPs in immersion freezing mode (Atkinson et al, 2013;Pinti et al, 2012;Kanji et al, 2017;Kaufmann et al, 2016;Boose et al, 2016;Kumar et al, 2018;2019a;2019b).…”
Section: Introductionmentioning
confidence: 99%